2008
DOI: 10.1038/ncpcardio1397
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic shear stress and the endothelium in cardiovascular pathophysiology

Abstract: SUMMARY Endothelium lining the cardiovascular system is highly sensitive to hemodynamic shear stresses that act at the vessel luminal surface in the direction of blood flow. Physiological variations of shear stress regulate acute changes in vascular diameter and when sustained induce slow, adaptive, structural-wall remodeling. Both processes are endothelium-dependent and are systemically and regionally compromised by hyperlipidemia, hypertension, diabetes and inflammatory disorders. Shear stress spans a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
852
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,002 publications
(874 citation statements)
references
References 75 publications
(88 reference statements)
11
852
0
11
Order By: Relevance
“…Increase in cardiac output could alter mean fluid shear and affect NO production, as occurs with exercise and as others have reported (15,16,28,31,37). We have not directly measured cardiac output in rats in response to pG z .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Increase in cardiac output could alter mean fluid shear and affect NO production, as occurs with exercise and as others have reported (15,16,28,31,37). We have not directly measured cardiac output in rats in response to pG z .…”
Section: Discussionmentioning
confidence: 88%
“…Low-amplitude pulses to the circulation through periodic acceleration induces endothelial-dependent vasodilatation. J Appl Physiol 106: 1840 -1847, 2009. First published March 26, 2009 doi:10.1152/japplphysiol.91612.2008.-Low-amplitude pulses to the vasculature increase pulsatile shear stress to the endothelium.…”
mentioning
confidence: 99%
“…A well‐established concept in arterial endothelial biology is the cause–effect relationship between hemodynamic WSS and gene expression 1, 28, 29, 30. In this study, we identified the regional patterning of WSS and EEC phenotype but have not yet isolated the mechanisms to explain their relationships and how they may be different or similar to arterial ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Both these conditions, according to Laplace law, make these plaques highly susceptible to rupture [13,31]. Moreover, it has to be emphasized that these calcified nodules, protruding into the vascular lumen, can induce flow disturbances, increase the stiffness and reduce the elasticity of the vessel wall [32].…”
Section: Discussionmentioning
confidence: 99%